Chronic Wasting Disease: Investigations on Prion Shedding and Risk of Transmission to Caribou ... - Cheng, Yo Ching (Graduate Studies, 2016)
Chronic wasting disease (CWD) is a transmissible prion disease affecting cervids mainly in North America. The responsible agent for this disease is the protease-resistant and infectious prion protein isoform (PrPSc) which is converted from a normal host-encoded glycoprotein (PrPC). In this study, I employed a novel in vitro amplification assay; the real-time quaking-induced conversion assay (RT-QuIC) to detect CWD prions in feces. I demonstrated the use of optimized RT-QuIC to define the shedding pattern of CWD prions in feces during the course of CWD. Additionally, I analyzed the distribution of PrP polymorphism among caribou populations in Alberta. The results permit predictions on the probability of CWD transmission to caribou populations. My studies provide a new tool to improve CWD surveillance and transmission risk assessment, and may be useful for CWD management in the future. ...